A Call to the Front: Occupational Therapy Practice in Addressing School Bullying. (April 2022) - Njelesani, Janet; Faulkner, Aisha; Schweitzer, Beth; Jeon, Hayden
Students with disabilities are more likely to be bullied at school than nondisabled students. This study aimed to understand occupational therapists' practices and roles in addressing bullying against students with disabilities. An electronic survey was distributed in the United States to school-based occupational therapists to collect information on roles, practices, and barriers in addressing bullying. Data were analyzed using inferential statistics, frequencies, percentages, and content analysis. A total of 151 occupational therapists participated. The results illuminated critical gaps in occupational therapy practice. The majority of occupational therapists see or hear of bullying but do not address it. They reported the lack of evidence and interventions to draw upon and time due to caseload as key barriers. Occupational therapists can contribute to anti-bullying practices as a member of the interprofessional team, bringing in strategies and interventions from occupational therapy to create safer environments for all students.